Utility of a Card-Type Respiratory Rate Measuring Device for Spontaneously Breathing Patients - Yoshiaki Iwashita; Shun Takeda; Satoshi Kawashima; Shinya Sato; Satoru Nebuya (Diagnostics)
Background/Objectives: Accurate measurement of respiratory rate (RR) is critical for early detection of patient deterioration. A newly developed contactless card-type device measures RR and heart rate (HR) by detecting chest impedance changes. Although previously validated in mechanically ventilated patients with 15% RR accuracy, its performance in spontaneously breathing patients remains uncertain. Methods: This prospective observational study was conducted at the Department of Emergency and Critical Care Medicine, Shimane University Hospital, in December 2022. Patients admitted to the emergency center without invasive mechanical ventilation were enrolled. The card-type device was subsequently placed on the left chest, while the RR and HR were simultaneously recorded with an electrocardiogram monitor. Data from both devices were collected and compared. Results: Six patients were enrolled. The RR measurements from the card-type device were within a 10% difference from those measured using the standard monitor in four out of six cases. In two cases, the card-type device recorded an RR lower than that of the standard monitor, which coincided with periods of patient speaking. For HR, the card-type device was within a 10% margin of the standard monitor in two cases, but it underestimated HR in the remaining four cases, particularly during high tidal volumes or increased thoracic thickness. Conclusions: The contactless card-type device accurately measured respiratory rates within a 10% margin compared to standard monitors in most non-intubated patients, except during activities such as speaking. Further studies with larger sample sizes are warranted to confirm these findings and improve the device’s performance.